Cambridge Ielts intensive training writing : (Tổng hợp, 2014)
As far as this book is concerned, it is arranged into 9 units whose themes centre upon the two tasks of the IELTS Writing test. Most frequently given topics in the IELTS Writing test are selectively provided so that can be well prepared for your coming actual test. Noticeably, each title question is followed by one or two sample answers. Moreover, lists of useful academic expressions folowing each essay sample answer or well-written sentences for some types of reports will undoubtedly help you with the most relevant language for your Acedemic Writing test.